Mal- estar na adolescência contemporânea, constituição subjetiva e laço social: diálogos entre psicanálise e educação - Antonelli, Claudia Maio (2022)
This dissertation presents the Master's Research in Education, which aimed to investigate the possible relationships between malaise in contemporary adolescence and the social bond, seeking elements that contribute to the educational practice of adolescents. Faced with the increasing suffering of adolescents and the difficulties mentioned by parents and teachers in connecting them, our research problem sought to answer the following question: How has psychoanalysis understood the malaise in contemporary adolescence and brought contributions to its management On education? For this, we listed the following categories of analysis: “discomfort and adolescence”, “adolescence and the subjective constitution of the subject”, “adolescence and social bond”, “adolescence, psychoanalysis and education”. Our investigation was based on a qualitative research methodology, through a Bibliographic Review based on the psychoanalytic theory of Freud, Lacan and other thinkers of contemporary psychoanalysis. Furthermore, the theme of malaise, as an existential condition, is inscribed in the history and culture of society, requiring that its approach include other knowledge, such as sociology, history, anthropology, politics and philosophy. In this sense, the method used was chosen, Dialectical Historical Materialism, which enabled a contextualized analysis of the reality of the investigated theme. We focus, therefore, on the relationship of the social bond with the subjective construction and the malaise of the teenager of our time In recent decades, the rise of capitalism and the scientifictechnological sudden changes in the social scenario, also establishing changes in the social bond that permeates education. The current capitalist discourse does not favor the establishment of the social bond; on the contrary, it reinforces individualism and impoverishes the references that in modern times ordered society. As a consequence, adolescents find themselves “unmapped” and helpless, a situation that is reflected in the manifestations of their malaise, including in the school environment. With this research, we found that the educational field and pedagogy can make use of psychoanalytic theory to understand the links between malaise, adolescence and contemporaneity, favoring the crossing of adolescence towards the social bond. Appropriating the psychoanalytical precepts allows the teacher to realize the existence of the unpredictability of the unconscious, in itself and in the adolescent student, allowing the flexibility of their discourse and the handling of transference. By assuming the posture of Listening, the master promotes the emergence of the subject and awakens the desire to know in his students.